2012
DOI: 10.1016/j.healun.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Decision tree for adjuvant right ventricular support in patients receiving a left ventricular assist device

Abstract: Background Right ventricular (RV) failure is a significant complication following implantation of a left ventricular assist device (LVAD). It is therefore important to identify patients at risk a-priori. However, prognostic models derived from multivariate analyses have had limited predictive power. Methods This study retrospectively analyzed 183 patient records of LVAD recipients between May 1996 and Oct. 2009; 27 of which later required a right ventricular assist device (RVAD+) and 156 remained on LVAD onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 34 publications
(41 reference statements)
3
78
0
2
Order By: Relevance
“…[5][6][7][8][9] Most studies have reported the incidence encompassing the need for inotropic support with or without RVAD (≥ 14 days) after LVAD implant, with a range of between 20.2% to 44%. [10][11][12] We know that prolonged RV failure (i.e., extended inotrope support) for more than 2 weeks is associated with adverse subsequent outcomes.…”
Section: Definition and Incidence Of Right Ventricular Failure After mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] Most studies have reported the incidence encompassing the need for inotropic support with or without RVAD (≥ 14 days) after LVAD implant, with a range of between 20.2% to 44%. [10][11][12] We know that prolonged RV failure (i.e., extended inotrope support) for more than 2 weeks is associated with adverse subsequent outcomes.…”
Section: Definition and Incidence Of Right Ventricular Failure After mentioning
confidence: 99%
“…Reverse remodeling of pulmonary vasculature can potentially occur by continuing unloading, and, unlike for heart transplantation, elevated pulmonary vascular resistance does not predict postimplant RVF. 7,11,12 Surrogates of reduced RV contractility, i.e., low pulmonary artery systolic pressure, and RV stroke work index remain markers of risk but have not yielded substantial predictive information. 8,10,12,16 A CVP/PCWP ratio > 0.63 was shown to be an independent predictor of early RVF risk in the HeartMate II Bridge-to-Transplantation Pivotal Trial population with overall low discrimination (0.68).…”
Section: Risk Factors and Risk Prediction Models For Rvf Postimplantamentioning
confidence: 99%
“…In this work, we use the algorithm C4.5, proposed by Quinlan, to improve the algorithm ID3 [46] and it is considered a standard model in supervised classification. The C4.5 has advantages such as its intuitive structure that is closer to clinical reasoning and therefore it can be more readily interpreted [47]. In addition, it performs implicitly variable screening or featuring selection [48].…”
Section: Decision Treesmentioning
confidence: 99%
“…Several algorithms exist to distinguish patients likely to require biventricular support, and this aspect is of critical importance because of the lack of optimal outcomes, especially in the setting of transplantationineligible patients. [17][18][19] …”
Section: Selection Of the Appropriate Patient For Lifetime Mcs Therapymentioning
confidence: 99%